2003
DOI: 10.1021/ic034685q
|View full text |Cite
|
Sign up to set email alerts
|

Homochiral Zn and Cd Coordination Polymers Containing Amino Acid−Tetrazole Ligands

Abstract: The reactions of (S)-3-cyanophenylalanine with NaN(3) in the presence of H(2)O and Lewis acids (ZnCl(2) and CdCl(2)) afford two unprecedented 3D homochiral networks, mono[(S)-5-(3-tetrazoyl)-phenylalaninato]zinc(II) (1) and mono[(S)-5-(3-tetrazoyl)-phenylalaninato]cadmium(II) monoaqua(II) (2), respectively. The two compounds are isostructural with noninterpenetrated SrAl(2) topology. The structure of these coordination polymers gives new insight into Sharpless' reaction of chiral 5-substituted 1H-tetrazole and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…For example, the modification of the phenyl ring in Phe with a tetrazole affords a 3-dimensional bio-MOF whereas 1-and 2-dimensional structures are common using a metal ion and non-modified Phe. [95] The two compounds, mono[(S)-5-(3-tetrazoyl)-phenylalaninato]zinc(II) and mono[(S)-5-(3-tetrazoyl)-phenylalaninato]cadmium(II) monoaqua reported by Li et al, were isostructural with a non-interpenetrated SrAl2 topology (Table 1, entry 17). [48] Rational design to adjust the "depth" and the "width" of the ligands showed that one could control the size and shape of the 2-dimensional Zn II and Cd II chiral bio-MOFs by introducing different functionalities into the phenyl ring.…”
Section: Ligand Design In Mofsmentioning
confidence: 94%
“…For example, the modification of the phenyl ring in Phe with a tetrazole affords a 3-dimensional bio-MOF whereas 1-and 2-dimensional structures are common using a metal ion and non-modified Phe. [95] The two compounds, mono[(S)-5-(3-tetrazoyl)-phenylalaninato]zinc(II) and mono[(S)-5-(3-tetrazoyl)-phenylalaninato]cadmium(II) monoaqua reported by Li et al, were isostructural with a non-interpenetrated SrAl2 topology (Table 1, entry 17). [48] Rational design to adjust the "depth" and the "width" of the ligands showed that one could control the size and shape of the 2-dimensional Zn II and Cd II chiral bio-MOFs by introducing different functionalities into the phenyl ring.…”
Section: Ligand Design In Mofsmentioning
confidence: 94%
“…that of 2 and 3. In fact, 3D coordination frameworks normally show higher robustness than the 1D and 2D ones [16,17].…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Thus, Qu et al 104 used L-(3-cyanophenyl)alanine (90) to form zinc complexes (for example, compound 91 in Scheme 32) and cadmium complexes containing the tetrazolyl derivative of phenylalanine as ligands.…”
Section: Scheme 31mentioning
confidence: 99%